2020
DOI: 10.1021/acsomega.0c02594
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Carbon/α-Fe2O3 Nanoleaf Composites for Disposable Nitrite Sensors and Energy Storage Applications

Abstract: In this work, we report a novel hydrothermal synthesis of α-Fe 2 O 3 nanoleaf-incorporated mesoporous carbon-chitosan (α-Fe 2 O 3 @MPC-chit) as a versatile disposable sensor for selective electrochemical detection of nitrite and for supercapacitor applications. The newly synthesized α-Fe 2 O 3 @MPC-chit nanocomposite was characterized by scanning electron microscopy, X-ray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Many transition-metal oxides (TMOs) have been studied for their good pseudocapacitance properties. It has been reported that the electrical performance of other carbon materials was enhanced by doping TMOs, such as mesoporous carbon, , carbon nanofibers, ,, and carbon nanosheets. , It is feasible to increase the energy storage properties by the combined use of TMOs and graphene. ,, Various groups have reported on the combined use of graphene and TMOs to overcome the drawbacks in the electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Many transition-metal oxides (TMOs) have been studied for their good pseudocapacitance properties. It has been reported that the electrical performance of other carbon materials was enhanced by doping TMOs, such as mesoporous carbon, , carbon nanofibers, ,, and carbon nanosheets. , It is feasible to increase the energy storage properties by the combined use of TMOs and graphene. ,, Various groups have reported on the combined use of graphene and TMOs to overcome the drawbacks in the electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…At the FT-IR spectrum of calcined Fe 2 O 3 /Na 2 WO 4 nanofibers, the loss of the corresponding CN and NH functional group bands has been shown to confirm successful calcination of PVP-Fe­(NO 3 ) 3 /Na 2 WO 4 nanofibers. The FT-IR spectrum of the CC-Fe 2 O 3 /Na 2 WO 4 NF electrode successfully adsorbed the Fe 2 O 3 /Na 2 WO 4 nanofiber layers by the tensile vibrational bands of these binary metal oxides which are shown in the range between 591 and 440 cm –1 (Figure a). , …”
Section: Resultsmentioning
confidence: 98%
“…The FT-IR spectrum of the 2a). 38,39 The prepared samples were further characterized by XRD to identify the purity and crystallite phase (Figure 2b). The XRD pattern of PVP-Fe(NO 3 ) 3 /Na 2 WO 4 NFs showed an amorphous peak at 20.1°assigned to the PVP structure.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicate that 1-CPE has the electrocatalytic activity for reducing KBrO 3 and NO 2 À . Accurate and rapid detection of nitrite in ecological environment by electrochemical technology is very important [41] due to the harmness to environment and human health brought by nitrite. Based on the good electrocatalytic behavior of 1-CPE, current analysis i-t technology was used to detect nitrite under the optimum conditions.…”
Section: Electrocatalysis and Sensing Behavior Of 1-cpementioning
confidence: 99%